2004
DOI: 10.1191/0269215504cr719oa
|View full text |Cite
|
Sign up to set email alerts
|

Well-being and instrumental activities of daily living after stroke

Abstract: 'Leisure activities' demonstrated the strongest association to subjective well-being as expressed by the 'satisfaction' dimension. In stroke rehabilitation leisure activities should be addressed when assessing function and planning intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 33 publications
5
55
0
2
Order By: Relevance
“…Poor IADL ability (NEADL score <20) may have impeded them from achieving their expectations, even after training, thus negatively affecting their mood outcome. This study lends support to the findings of previous studies that IADL is related to HRQOL and life satisfaction (Hartman-Maeir et al, 2007;Sveen et al, 2004).…”
Section: Evidence Regarding Age and Iadls On The Ss-qol Mood Domainsupporting
confidence: 90%
See 1 more Smart Citation
“…Poor IADL ability (NEADL score <20) may have impeded them from achieving their expectations, even after training, thus negatively affecting their mood outcome. This study lends support to the findings of previous studies that IADL is related to HRQOL and life satisfaction (Hartman-Maeir et al, 2007;Sveen et al, 2004).…”
Section: Evidence Regarding Age and Iadls On The Ss-qol Mood Domainsupporting
confidence: 90%
“…The literature has suggested that IADLs are related to QOL for stroke patients (Hartman-Maeir et al, 2007;Sveen, Thommessen, Bautz-Holter, Wyller, & Laake, 2004), and the IADL leisure domain is associated with well-being and life satisfaction after stroke (Sveen et al, 2004). Improved IADL ability after training appeared to accelerate recovery in some HRQOL domains (HartmanMaeir et al, 2007).…”
mentioning
confidence: 99%
“…When they return home, people who have had a mild stroke may have difficulty accomplishing complex life habits and may even have to abandon some of them. Changing the level of accomplishment of life habits, and especially their loss, can be detrimental to people's well-being and personal growth (23). Since 55% of the participants were under 66 years of age, the majority were at an age where they could still perform complex life habits without assistance and difficulty such as holding a paid job, and could live for many more years.…”
Section: Discussionmentioning
confidence: 99%
“…These include social support and social network (Osberg et al, 1988;Åström, Asplund, Åström, 1992;Nagayoshi, Iwata and Hachisuka, 2008), mental and physical disabilities (Osberg et al, 1988;Viitanen, Fugl-Meyer, Bernspang, and FuglMeyer, 1988;Åström, Asplund, Åström, 1992;Gottlieb, Golander, Bar-Tal and Gottlieb, 2001;Ostir et al, 2008), depression (Åström, Adolfsson, Asplund, and Åström, 1992;Lofgren, Gustafson and Nyberg, 1999;Edwards, Hahn, Baun, and Dromerick, 2006), meaningful lifestyles/leisure activities (Sveen et al, 2004;Edwards, Hahn, Baun, and Dromerick, 2006;Ekstam, Uppgard, Von and Tham, 2007;Hartman-Maeir et al, 2007a, 2007b, and return to work (Vestling, Tufvesson, and Iwarsson, 2003;Vestling, Ramel, and Iwarsson, 2005). Although there have been four studies, in Israel, Japan, and Iran (Hartman-Maeir et al, 2007a, 2007bNagayoshi, Iwata and Hachisuka, 2008;Dalvandi 6 et al 2010), life satisfaction after stroke has been studied primarily within Western countries.…”
mentioning
confidence: 99%